A percepção da fricativa coronal em coda medial por pessoenses - Henrique, Pedro Felipe de Lima (2016)
The primary objective of the present study is to analyze how listeners perceive the alveolar and palatal variants of /S/ in medial coda in their speech community (i) observing if the palatal/alveolar contrast is perceived in a different way, in a numerical scale, in different following phonetic-phonological contexts; (ii) verifying if listeners from João Pessoa are aware of the behavior of the variant in their own dialect; in other words, if they perceive what variant they use in relation to several following contexts; and (iii) verifying if the listeners from João Pessoa have a dialectal identity in relation to the behavior of the fricative in coda in João Pessoa, that is, if they believe that their pronunciation corresponds to the preferred one of their speech community in relation to the analyzed process. For that, three experiments of perception were developed and applied to listeners from João Pessoa: the first one consists of a task of identifying how different would be two productions of a same word in relation to /S/ in medial coda; the second one was to choose which of the two productions sounded more similar to the way people from João Pessoa speak; and the third one was to answer which of the two productions sounded more similar to the way the speaker himself/herself speaks. The stimuli were recorded by a speaker from João Pessoa. She is an undergraduate student in the 15-25 years age group. After recording the words in isolation, the files were matched to the pairs of stimuli that were presented to listeners through the website. The statistical analyses to test the hypotheses were carried out using the software R (R Core Team, 2013) from the subjects’ answers. The most relevant results were: (a) listeners attribute the same degree of difference to the pair of fricatives independently of the following context; (b) they are aware of the fricative’s behavior of João Pessoa’s dialect; and (c) there is identification between these speakers and the dialect of their speech community regarding the palatalization of coronal fricative. In order to develop the tests and to formulate hypotheses it was took into account studies concerning acoustic characteristics of fricatives in data of production and perception (KENT & READ, 1992; JONGMAN et al., 2000; JESUS, 1999; HAUPT, 2007; FERREIRA-SILVA et al., 2015; HENRIQUE et al., 2015), data of studies that analyzed the behavior of /S/ in coda in dialects of Brazil (CALLOU; LEITE; MORAES, 2002; BRESCANCINI, 2002, 2003; HORA, 2003, 2011; RIBEIRO, 2006; LIMA, 2013; LOPES, 2012) and the framework of the theory of linguistic variation and change (WEINREICH, LABOV & HERZOG, 1968; LABOV, 1972; ECKERT, 2008, 2012).